Takhassus Tahfidz Program in Formal Institutions: Implementation, Obstacles, and Solutions - Raikhan Raikhan; Bagas Mukti Nasrowi (Tadibia Islamika, 2022)
This research aims to describe the implementation of Takhassus Tahfidz program at the Formal Institution in Lamongan regency, the obstacles experienced during the implementation of the Tahfidz class, and the solutions offered from the obstacles experienced during the implementation of Tahfidz program. This research used a qualitative descriptive approach with case study research design. Data collection method used were observation, interview, and documentation. The data were validated through triangulation techniques. For data analysis technique, the researchers used qualitative analysis through the steps of data reduction, data presentation, and conclusion drawing or verification. The results of this study show that (1) the implementation of the Takhassus Tahfidz program at the formal institution in Lamongan regency is carried out with three stages of learning programs, planning (materials, media, methods: Bi Nadzhor, Talaqqi, and Taqrir, and time allocation); implementation (introduction, core: ziyadah and murojaah, and closing); then Evaluation (2) the obstacles faced during the implementation of the Takhassus Tahfidz program are environmental conditions, time management, personal matters, students’ motivation (low intention to memorize), the level of intelligence, and the student organization, (3) the solutions offered to overcome obstacles that occur during the implementation of the Takhassus Tahfidz program are by providing additional time; motivating the Tahfidz teachers, facilitating students with a cozy place to memorize, guiding students to manage time well, and prohibiting students to join student organization.